DIFFERENT FEEDING TIME PERIOD TO INCREASE GROWTH AND SURVIVAL RATE OF ASIAN REDTAIL CATFISH (Hemibagrus nemurus VALENCINNES, 1840) - Ikbal, Muhamad; Sukendi, Sukendi; Asiah, Nur (Asian Journal of Aquatic Sciences, 2022)
This research was carried out in November-December 2021 at the Fish Hatchery and Breeding Laboratory, Department of Aquaculture, Faculty of Fisheries and Marine, Universitas Riau. The purpose of this study was to determine the period and the best type of feed on the growth and survival rate of Asian redtail catfish. The method used Completely Randomized Design (CRD) with 4 levels of treatment, namely P1 (Artemia sp at the age of 4-12 days, Kutu air 13-19 days, and Tubifex sp 20-35 days), P2 (Artemia sp 4-10 days, Kutu air 11–15 days, and Tubifex sp 16–35 days), P3 (Artemia sp 4–12 days, kutu air 13–19 days, and artificial feed 20–35 days), and P4 (Artemia sp 4–10 days, kutu air 11–15 days, and artificial feed 16–35 days). Asian redtail catfish larvae that had run out of egg yolks were put into rearing containers with a density of 3 fish/L and reared for 35 days. Parameters measured in this study were absolute weight growth, absolute length growth, specific growth rate (LPS), survival rate (SR), and water quality. The results showed that the different feeding periods had a significant effect (P<0.05) on the growth and survival of Asian redtail catfish larvae. Treatment with Artemia sp at the age of 4-10 days, kutu air 11–15 days, and Tubifex sp. 16–35 days resulted in an absolute weight growth of 1.06 g, an absolute length growth of 4.23 cm, a specific growth rate of 11.94% and a survival rate of 84.44%. The water quality parameters during the study were temperature 26.4-27.5oC, pH 5.2-6.5 and dissolved oxygen 3.6-4.67 ppm.